2013
DOI: 10.1177/0300060513489471
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of A disintegrin and metalloproteinase 9 (ADAM9) mRNA as a promising novel marker for the detection of pulmonary sarcoidosis

Abstract: Aims: This prospective study investigated the potential role of serum A disintegrin and metalloproteinase 9 (ADAM9) mRNA in the differential diagnosis of pulmonary sarcoidosis from other diseases with similar clinical presentations, such as tuberculosis (TB). Methods: Serum samples were collected from patients with sarcoidosis, and compared with those from patients with TB and healthy control subjects. Real-time quantitative reverse transcription-polymerase chain reaction was performed to measure the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, discovering sensitive and specific biological markers of TB would not only provide new insights for the molecular and cellular processes involved in pathogenicity, but also establish a fast, sensitive and efficient way for diagnosis and treatment. Many studies have explored the potential biomarkers for the diagnosis and treatment of TB [ 4 , 5 , 6 , 7 , 8 ]. For instance, Sahin et al suggested that a high molecular weight mucin-like glycoprotein CA-125, remarkably increased in active pulmonary TB compared to that in inactive TB or normal sample, may be a biomarker of pulmonary tuberculosis activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, discovering sensitive and specific biological markers of TB would not only provide new insights for the molecular and cellular processes involved in pathogenicity, but also establish a fast, sensitive and efficient way for diagnosis and treatment. Many studies have explored the potential biomarkers for the diagnosis and treatment of TB [ 4 , 5 , 6 , 7 , 8 ]. For instance, Sahin et al suggested that a high molecular weight mucin-like glycoprotein CA-125, remarkably increased in active pulmonary TB compared to that in inactive TB or normal sample, may be a biomarker of pulmonary tuberculosis activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%